2014
DOI: 10.1080/14786419.2014.947490
|View full text |Cite
|
Sign up to set email alerts
|

Aedes aegyptilarvicide from the ethanolic extract ofPiper nigrumblack peppercorns

Abstract: Due to unavailability of a vaccine and a specific cure to dengue, the focus nowadays is to develop an effective vector control method against the female Aedes aegypti mosquito. This study aims to determine the larvicidal fractions from Piper nigrum ethanolic extracts (PnPcmE) and to elucidate the identity of the bioactive compounds that comprise these larvicidal fractions. Larvicidal assay was performed by subjecting 3rd to 4th A. aegypti instar larvae to PnPcmE of P. nigrum. The PnPcmE exhibited potential lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 7 publications
0
13
0
1
Order By: Relevance
“…Piperine, one of the major pungent constituents of Piper nigrum , has been found to possess interesting pharmacological effects. Increasing evidence from in vitro and in vivo studies has shown that it possesses anticancer [ 20 , 21 ] and neuroendocrine modulator effects [ 22 ]. A few studies have demonstrated its expectorant, antiflatulent and cholesterol-lowering properties [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Piperine, one of the major pungent constituents of Piper nigrum , has been found to possess interesting pharmacological effects. Increasing evidence from in vitro and in vivo studies has shown that it possesses anticancer [ 20 , 21 ] and neuroendocrine modulator effects [ 22 ]. A few studies have demonstrated its expectorant, antiflatulent and cholesterol-lowering properties [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Masing-masing perlakuan dilakukan replikasi sebanyak empat kali replikasi sesuai standart bioassay WHO 2005. 5…”
Section: Metodeunclassified
“…Black pepper is the dried ripe fruit of Piper nigrum L., previous studies have revealed its chemical compositions (amide alkaloids, terpenoids, multimeric alkaloids and volatile oil) and activities (immunomodulatory, stimulatory, larvicidal, anti-inflammatory, antioxidant, antifertility, antiulcer, antifungal, antibacterial and anticholinesterase activities) (Ingkaninan et al 2003;Meghwal & Goswami 2013;Santiago et al 2015). During our search for ChEIs from natural resources, 95% ethanol extract of P. nigrum showed promising dual AChE-BChE inhibition activity ( Figure S1).…”
mentioning
confidence: 92%